Moderating effect of technology readiness on the relationship between electronic tax invoice adoption and its determinants among small and medium enterprises in Embakasi sub-county, Nairobi, Kenya - Peter Kinuthia; Philip Kiprotich; Risper Achieng (PT. Global World Scientific, 2026)
The purpose of this study was to examine the moderating effect of technological readiness on the relationship between perceived benefit, perceived security, relational trust and the adoption of electronic tax invoices among small and medium enterprises (SMEs) in Kenya. Guided by the Innovation Diffusion Theory, the Technology Acceptance and Use of Technology Theory, and the Standard Economic Theory, the study employed an explanatory research design targeting 859 SMEs in Embakasi Sub-County. A sample of 273 SMEs was selected through stratified and simple random sampling techniques. Data were collected using semi-structured questionnaires and analyzed using descriptive and inferential statistics, including regression analysis. The findings revealed that perceived benefit, perceived security, and relational trust all had positive and statistically significant effects on electronic tax invoice adoption. Additionally, technological readiness was found to significantly moderate these relationships, enhancing the adoption process. The study supports theoretical perspectives emphasizing the importance of perceived advantages, trust, and security in technology adoption. It recommends that SME managers focus on improving technological readiness and trust-building initiatives, while policymakers should invest in supportive legal frameworks, digital infrastructure, and capacity building to drive broader adoption of electronic tax systems among SMEs.